Analysis Of Hazardous And Toxic (B3) Solid Waste Management At The Regional General Hospital (RSUD) Duri District Mandau: Analisis Pengelolaan Limbah Padat Bahan Berbahaya Dan Beracun (B3) Di Rumah Sakit Umum Daerah (RSUD) Duri Kecamatan Mandau Tahun 2022 - Prasika Nilasari; Raviola Raviola; Nurvi Susanti; Emy Leonita; M. Kamali Zaman (Badnur Medisa Group, 2022)
Hazardous and Toxic Materials hereinafter abbreviated as B3 are substances, energy, and/or other components which due to their nature, concentration and/or amount, either directly or indirectly, can pollute and/or damage the environment, and/or endanger the environment. health, and the survival of humans and other living things. The Mandau District General Hospital (RSUD) has a bed capacity of 172 beds with a total of 439.991 visits in 2021. With the high number of inpatient beds, it shows the amount of waste generated every day. Waste income at the Mandau District Hospital in 2021 for medical waste amounted to 21,298.5 kg and medical waste for syringes amounted to 7,693.3 kg. It was also found in B3 solid waste management that was not in accordance with the Regulation of the Minister of Environment and Forestry No. 56 of 2015. This research method used a qualitative research design with a phenomenological approach. The results of this study indicate that there are policies and SOPs even though their implementation is not appropriate, human resources are sufficient according to the background of S1 Environmental Health, the use of PPE is still incomplete, there is a reduction process that has been carried out such as recycling jerry cans as a substitute for syringe safe boxes that are not used. has a clear symbol or code, the segregation of waste is not appropriate because the plastic used is only in the form of 2 types, namely infectious and non-infectious, temporary storage is carried out in cold storage where there is an infectious and non-infectious plastic wrapping in the waste which is made into a single bond.